Risk factors of sleep-disordered breathing among Public Transport Drivers of Kochi, India - Shadananan, Vishnu; Sapna, Varma N.K.; Prabha, Rahul D.; Ajith, V.V.; Ghosh, Parvathy (International Journal of Occupational Safety and Health, 2023)
Introduction: Sleep-disordered breathing (SDB) appears to be a major occupational health concern among transport drivers as it increases the chance of road traffic crashes. The study aimed to determine the prevalent risk factors of sleep-disordered breathing in public transport drivers of Kochi, India. Methods: A descriptive cross-sectional study was performed among 50 public transport drivers who satisfied the inclusion criteria and were categorized as high and low-risk groups using the STOP-BANG questionnaire. Physical examination recorded Neck circumference, waist-hip ratio, body mass index, blood pressure, and facial profile. Excessive daytime sleepiness was evaluated using the Epworth sleepiness scale. Mann Whitney and Chi-square tests were used to test for significance. Logistic regression was also done by including the significant variables. Results: The high risk (n= 27) and low-risk groups (n=23) were identified. Among the high-risk group; age, body mass index, neck circumference, blood pressure, snoring and tiredness showed statistically significant results (p<0.05) when compared to the low-risk group. Excessive daytime sleepiness was present among 29.6% of high-risk subjects. Logistic regression confirmed that age (OR=1.176; p=0.001) and body mass index (OR=1.348; p=0.050) were independent predictors of developing a high risk of SDB. Conclusion: mong public transport drivers in Kochi, India; older age and increased body mass index were significant contributing factors to developing sleep-disordered breathing. Obstructive sleep apnea (OSA), whether diagnosed or undiagnosed, is a major public health concern and a proven risk factor for vehicle crashes. Applicants for public transport driver's licenses should be thoroughly examined for the risk of OSA/SDB. A standardized screening protocol for OSA risk assessment should be advisable for public transport drivers to ensure road safety.